A multidimensional analysis of corporate governance and hospitality environment in the private Brazilian hospital sector. (14th June 2019) - Schwack, Cristiane Garrido; Monken, Sonia Francisca De Paula; Motta, Lara Jansiski; Biancolino, César Augusto
This study evaluated the corporate governance practices of hospitals affiliated with the National Association of Private Hospitals (NAPH). This was a quantitative study of descriptive nature, which utilised the ex post facto research strategy and employed the multidimensional scaling technique of accounting data, hospitality environment and corporate governance practices gathered from the hospital websites. It was found that hospitals that showed more adherence to corporate governance practices presented the best financial indicators and outlook. Thus, the result showed a positive application of corporate governance practices.